Analysis of the Structure And Composition of The Production Forest Floor Vegetation in Nenuk, Naekasa Village, Tasifeto Barat District, Belu Regency - Kolo, Erlinda Desi; Seran, Yoseph Nahak; Ledheng, Ludgardis (Metamorfosa: Journal of Biological Sciences; Vol 9 No 2 (2022)DO - 10.24843/metamorfosa.2022.v09.i02.p08, 2022)
The pupose of this study was to identify the types of forest floor vegetation, the sctructure and composition of the forest floor vegetation and environmental factors that influence the growth of forest floor vegetation in the Nenuk Production forest area. Data collection was carried out in the Nenuk Production forest ,Naekasa village, Tasifeto Barat district, Belu regency usingplots as many as 25 observating plots with a size 2m x 2m  . From the result of study found 18 types of floor vegetation consisting of 13 families, forest floor vegetation which has the highest important value index of the Seedling level is the Tectona grandis , L.with INP by 94,74%, at the Herbs level is Ottochloa nodosa , Kunth. with INP by 74,79%, at the bush level is Flemingia strobilfera , L.with INP by 58,32%, at the Shrub level is Passiflora foetida , L. with INP by 79,19% .Enviromental factors affecting the growth of forest floor vessel forestry production of the Nenuk production is the temperature, humidity and the pH with an average temperature of 31,7ºC, moisture 68,8% and  pH 6,8. The sctructure and composition of the Nenuk production forest needs to be preserved to maintain the balance of he Nenuk production forest ecosystem in the future.